Sistem Pendukung Keputusan Rekrutmen Desainer Grafis Di Ss Bordir Menerapkan Metode Additive Ratio Assessment (ARAS) - Shakya Suci Kamara; Nelly Astuti Hasibuan; Fince Tinus Waruwu (STMIK Budi Darma, 2022)
Graphic designer recruitment problem is faced by SS Embroidery, that is, according to several different criteria and different evaluation weights, it is difficult to make a decision to determine the graphic designer problem when the evaluation process is objective, which leads to the final decision. Therefore, to overcome the problems faced by companies in SS embroidery, a decision support system is needed to select prospective graphic designers. When choosing a method, it is necessary to use the additive ratio assessment method (ARAS). The system will obtain a ranking decision based on each alternative choice based on a number of predetermined criteria. The alternative with the most weights is the recommended alternative. To realize the decision support system, a decision support system application program is designed. Designed using the Visual Basic 2008 application, which is designed only for user convenience, through the application of this decision support system, it is expected to facilitate the recruitment of prospective graphic designers at SS Embroidery so that the selection of graphic designers is expected to get the best results from the Additive Ratio Assessment (ARAS) method. It is hoped that the ARAS method can provide assistance to the company in determining the recruitment of graphic designers. The results of the Decision Support System for the recruitment of graphic designers are Alternative A6 with a value of 1,307 on behalf of